Molecular modeling of (1010) and (0001) zinc oxide surface growth from solution: islands, ridges and growth-controlling additives - Milek, Theodor; Zahn, Dirk (Crystengcomm, 2015)
The mechanism of (1010) and (0001) zinc oxide surface growth from ethanolic solution is investigated by molecular simulation. Growth steps are modelled at the maximum level of detail, i.e. by association of individual Zn2+ and OH- ions. Apart from structural relaxation, a mixed quantum/classical approach is used to explicitly study the proton-transfer reactions during crystal growth. Starting from idealized surfaces, we find that the (0001) face evolves into rough landscapes composed of small islands separated by 1 nm. On the other hand, the (1010) growth front shows the formation of ridges encompassed by analogous 1010 planes of the wurtzite structure. Contrary to idealized surface models, such rough surfaces obtained from explicit growth simulations enable us to identify considerable differences in both the binding site and energy for the association of growth-controlling additives. Using acetate and citrate ions as examples, we demonstrated the preferential association with peaks and kinks, respectively.
EAM Import::2019-03-12